TINJAUAN YURIDIS RANGKAP JABATAN WAKIL MENTERI BADAN USAHA MILIK NEGARA MENURUT UNDANG-UNDANG NOMOR 39 TAHUN 2008 TENTANG KEMENTERIAN NEGARA - Yanti, Anisya Ismi; Indra, Mexsasai; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Indonesia is a constitutional state which is not only based on power, but onexisting rules or laws. The government runs on the basis of the constitution and isnot absolutism (unlimited power) in accordance with the Provisions contained inArticle 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia whichstates that Indonesia is a state of law.The presidential system is a system of government that is centered on theposition of the president as head of government as well as head of state. In thissystem, the executive branch, which is represented by the president, is notresponsible to the legislature, which, if exemplified in the Indonesian governmentsystem, is represented by the DPR. The position of the executive body is strongerin dealing with the legislature. A presidential system can be said to be arepresentative government of the people, with a system of strict separation ofpowers. The separation between the executive and legislative powers means thatthis executive power is held by an agency or organ which, in carrying out itsduties, is not responsible for the people's representative body.This concurrent position in the Ombudsman's assessment will causeseveral losses. Starting from the existence of conflicts of interest, issues ofcompetence and capability of officials who are concurrently not in accordancewith the position of commissioner, and the emergence of double income. In theview of the State Civil Apparatus Commission (KASN), the phenomenon ofmultiple positions apart from causing a conflict of interest, is also the root offraud. Concurrent positions of SOE commissioners by public officials areopportunities for corruption.Multiple Positions is an action carried out by a person in two or morepositions in the same or different environments. Being in power means that whena person has concurrent positions, it is undeniable that the holder of the positionwill not be able to optimally carry out one of the positions held due to negligence.So that the worst possibility is not carrying out the duties optimally in bothpositions.Keywords: Multiple Positions, Minister, Position, Constitutional Court.